Preparation method of fluorinion-induced manganese oxide composite material and application of fluorinion-induced manganese oxide composite material as positive electrode material in aqueous magnesium ion capacitor
By induced manganese oxide composite material as the positive electrode material, the reaction restriction problem caused by water decomposition during the charging and discharging of magnesium ion batteries is solved, and a water-based magnesium ion capacitor with high specific capacitance and long discharge time is achieved, and the process is simple and cost is low.
Patent Information
- Application Number
- CN202411796418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
During the charging and discharging process, magnesium ion batteries are prone to oxygen evolution reactions and hydrogen evolution reactions due to the potential decomposition of water, which limits the working voltage between the electrode materials and is not conducive to the electrochemical reaction. Moreover, divalent Mg2+ ions have a strong electrostatic effect on the host, resulting in slow diffusion kinetics and low reversible specific capacity.
The fluorine ion-induced manganese oxide composite material is used as the positive electrode material. The MnO2 nanoflower is obtained by dissolving potassium permanganate and manganese sulfate in deionized water, and then hydrothermal reaction is carried out with substances such as manganese chloride, potassium fluoride and polyvinylpyrrolidone to form the MnO2/Mn2O3/KMnF3 composite material. The composite material has better electronic conductivity and higher work function, which can effectively alleviate Jahn-Teller distortion and improve the stability and cycling performance of the material.
The specific capacitance of the aqueous magnesium ion capacitor is significantly improved, the discharge time is increased by about 1500 seconds, the specific capacitance is as high as 209.56F/g, which is about 1.6 times larger than the original MnO2. The material has high specific capacitance and good adaptability and electrolyte, which is simple in process and low in cost.
Smart Images

Figure CN119626793A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and relates to a preparation method of a fluoride ion induced manganese oxide composite material and an application of the composite material as a positive electrode material in an aqueous magnesium ion capacitor. Background Art
[0002] In the past decade, the focus has shifted significantly from efficient energy harvesting from solar, wind, thermal and biofuel sources to energy storage and collection through electrochemical means such as rechargeable batteries and supercapacitors. The great interest in developing sustainable electrochemical devices to store and collect energy has promoted the development of hybrid electric vehicles, smart grids, portable electronic products, etc. In recent years, lithium-ion batteries have been widely used in various portable electronic devices and automobiles, achieving great success and economic benefits. However, due to the low crustal reserves of lithium, high production costs, low volumetric power density, especially the use of organic electrolytes and battery safety, the development and application of lithium-ion batteries have been greatly restricted, and the search for energy storage devices to replace lithium-ion batteries has therefore been booming. In recent years, there have been endless reports of safety accidents such as explosions of electronic products powered by lithium-ion batteries. Therefore, it is crucial to develop a clean, green and highly safe energy system. In addition to lithium-ion battery technology, researchers are paying increasing attention to magnesium-ion batteries. Compared with the standard hydrogen electrode, the negative reduction potential of the Mg anode is -2.37V, close to the lithium electrode, and has a lower tendency to form dendrites, so it can provide high energy and stable performance. Compared with lithium-ion batteries, magnesium-ion batteries also have higher material abundance (about 2.9% of the earth's crust reserves), high theoretical volume capacity (about 3833mAh / cm 3 ), higher safety and lower cost. The biggest challenge facing magnesium-ion batteries is the potential decomposition of water during charge and discharge (GCD). The thermodynamic potential of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) caused by water electrolysis will limit the working voltage between electrode materials, which is not conducive to the electrochemical reaction. For the positive electrode material, divalent Mg 2+ Ions have a strong electrostatic effect on the host, resulting in slow diffusion kinetics and low reversible specific capacity. Therefore, the search for hierarchical porous structure cathode materials with large specific surface area can provide more active sites and shorten the Mg 2+ The diffusion distance of ions is more conducive to the embedding and extraction of magnesium ions, thus improving the cycle performance. Summary of the invention
[0003] The purpose of the present invention is to use a manganese-based fluoride composite material as a positive electrode material in an aqueous magnesium ion capacitor, and the provided aqueous magnesium ion capacitor has significantly improved specific capacitance.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A fluoride ion induced manganese oxide composite material, the preparation method of which comprises the following steps:
[0006] 1) adding potassium permanganate and manganese sulfate into deionized water, dissolving them by magnetic stirring, performing hydrothermal reaction to obtain a precursor, and then calcining to obtain MnO2 nanoflowers;
[0007] 2) The prepared MnO2 nanoflowers, manganese chloride, potassium fluoride and polyvinyl pyrrolidone are added to polyethylene glycol in sequence, and then ultrasonically dispersed and magnetically stirred to make them evenly dispersed. The solution is transferred to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction, centrifuged and washed, and dried to obtain a MnO2 / Mn2O3 / KMnF3 composite material.
[0008] Furthermore, in the above-mentioned method for preparing a fluoride ion induced manganese oxide composite material, in the MnO2 / Mn2O3 / KMnF3 composite material, the mass ratio of MnO2:KMnF3 is 4:1.
[0009] Furthermore, in the above-mentioned method for preparing a fluoride ion induced manganese oxide composite material, in step 1), the hydrothermal reaction is carried out at 140° C. for 2 hours.
[0010] Furthermore, in the above-mentioned method for preparing a fluoride ion induced manganese oxide composite material, in step 2), the hydrothermal reaction is carried out at 180° C. for 12 hours.
[0011] Application of the fluoride ion induced manganese oxide composite material described in any one of the above as a positive electrode material in an aqueous magnesium ion capacitor.
[0012] Furthermore, the above application method comprises the following steps:
[0013] 1) Preparation of positive electrode: After the MnO2 / Mn2O3 / KMnF3 composite material is uniformly mixed with the binder and the conductive material, a small amount of NMP is added as a dispersion liquid. After uniform mixing, the slurry is directly applied on the substrate carbon paper, dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and punched using a punching machine to obtain a positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material;
[0014] 2) Preparation of negative electrode: After the activated carbon is mixed with the binder and the conductive material, a small amount of NMP is added as a dispersion liquid. After mixing evenly, the slurry is directly applied on the substrate carbon paper, dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and punched using a punching machine to obtain a negative electrode sheet coated with activated carbon;
[0015] 3) Preparation of aqueous magnesium ion capacitors: Place the prepared negative electrode sheet coated with activated carbon into the center of the negative electrode shell, then place the diaphragm into the negative electrode shell, and drip the electrolyte to fully wet the diaphragm, then contact one side of the positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material with the wetted diaphragm, finally place the gasket and the shrapnel, and after packaging, obtain an aqueous magnesium ion capacitor.
[0016] Furthermore, in the above application, the binder is carboxymethyl cellulose or polyvinylidene fluoride.
[0017] Furthermore, in the above application, the conductive material is acetylene black or Super P.
[0018] Furthermore, in the above application, the electrolyte is any one of MgSO4 solution, MgCl2 solution and Mg(NO3)2 solution.
[0019] Preferably, the concentration of the electrolyte is 0.5M, and the amount added is 200 μL.
[0020] Furthermore, in the above application, the membrane is any one of a glass fiber membrane, a polypropylene membrane, a filter paper membrane and a polymer semipermeable membrane.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention designs a novel aqueous magnesium ion asymmetric capacitor, using MnO2 / Mn2O3 / KMnF3 composite material and activated carbon as positive and negative electrode materials respectively. It has the following advantages: First, the composite of MnO2 and KMnF3 can make the material have better electronic conductivity and higher work function; second, the introduction of F ions with strong electronegativity breaks the electronic symmetry of MnO6 octahedron, effectively alleviates Jahn-Teller distortion, and the joint action of Mn-O bond and Mn-F bond improves the stability of the material to a certain extent and enhances the long cycle performance; third, the synergistic effect of the composite structure of MnO2 and KMnF3 is more conducive to accelerating the diffusion kinetics of magnesium ions and has a lower migration barrier; fourth, a new phase Mn2O3 is formed in the process of MnO2 and KMnF3 composite, and the three-phase composite synergistic effect can effectively increase the specific surface area and pore size of the material, provide more active sites during the charge and discharge process, and facilitate the insertion and removal of magnesium ions.
[0023] 2. The present invention adopts a fluoride ion induced manganese oxide composite material as a positive electrode material to prepare an aqueous magnesium ion capacitor. After compounding with KMnF3, the discharge time is increased by about 1500 seconds, and the specific capacitance is as high as 209.56F / g, which is about 1.6 times that of the original MnO2.
[0024] 3. The original synthetic materials selected in the present invention have the characteristics of being cheap, environmentally friendly, recyclable and non-toxic. The prepared MnO2 / Mn2O3 / KMnF3 composite material also has a high specific capacitance and is highly compatible with the selected electrolyte.
[0025] 4. The present invention uses a MnO2 / Mn2O3 / KMnF3 composite material as the positive electrode material and activated carbon as the negative electrode material. The method has a simple synthesis process, a simple assembly process, is environmentally friendly, and has a low cost. It is expected to become an ideal green energy-saving energy storage device in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is the XRD spectra of MnO2 nanoflowers, KMnF3, and MnO2 / Mn2O3 / KMnF3 composite materials prepared by the present invention.
[0027] Figure 2 It is the SEM spectrum of the MnO2 / Mn2O3 / KMnF3 composite material prepared by the present invention.
[0028] Figure 3 It is a time-voltage diagram of an asymmetric aqueous magnesium ion capacitor assembled with the MnO2 / Mn2O3 / KMnF3 composite material prepared by the present invention and activated carbon.
[0029] Figure 4 This is a comparison chart of the specific capacitance of an asymmetric aqueous magnesium ion capacitor assembled with the MnO2 / Mn2O3 / KMnF3 composite material prepared by the present invention and activated carbon and an asymmetric aqueous magnesium ion capacitor assembled with original MnO2 and activated carbon. DETAILED DESCRIPTION
[0030] Example 1
[0031] (I) The preparation method of the original manganese dioxide material is as follows:
[0032] 0.5 g potassium permanganate and 0.2 g manganese sulfate monohydrate were added to 80 mL deionized water, and the two were fully dissolved after magnetic stirring for 1 hour. The solution was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and subjected to hydrothermal reaction at 140°C for 2 hours to obtain a manganese dioxide precursor. After centrifugal washing and drying, it was calcined at 360°C for 2 hours in an oxygen atmosphere to obtain manganese dioxide nanoflowers.
[0033] (ii) Fluoride ion-induced manganese oxide composite material, the preparation method is as follows:
[0034] 0.002 mol of tetrahydrated manganese chloride, 0.005 mol of dihydrated potassium fluoride, 0.2 g of polyvinyl pyrrolidone, and 0.8 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, and ultrasonically dispersed for 30 min, and then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 4:1.
[0035] (III) Detection
[0036] Figure 1 : is the XRD spectrum of the manganese dioxide nanoflower and fluoride ion induced manganese oxide composite material prepared in this embodiment. Figure 1 It can be seen that after the hydrothermal reaction, the obtained material is a composite material of MnO2 (PDF#72-1982) and KMnF3 (PDF#84-0442). After compounding, we found that in addition to the diffraction peaks of MnO2 and KMnF3, there is a Mn2O3 diffraction peak at 2θ=33.013°. This is because the F ions were introduced during the hydrothermal process, causing the MnO2 to undergo a crystal transformation from 2D layered to rod-like. This transformation is due to the shearing and curling of the MnO2 layer, which leads to the destruction of the Mn-O framework and the formation of low-coordinated Mn. From the electronic structure, it is found that the low-coordinated Mn ions have a higher spin, up to 3.7, indicating that these Mn are reduced to Mn during the reaction. 3+ This can also explain the strong diffraction peak of Mn2O3 at 2θ=33.013°.
[0037] Figure 2 is a SEM spectrum of the fluoride ion-induced manganese oxide composite material prepared in this example. Figure 2 It can be seen that the fluoride ion-induced manganese oxide composite material has a large number of small particles attached to the surface of the large flower cluster structure, which significantly increases the specific surface area of the material.
[0038] Example 2
[0039] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0040] 0.002 mol of tetrahydrated manganese chloride, 0.005 mol of dihydrated potassium fluoride, 0.2 g of polyvinyl pyrrolidone, and 3.8 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, and ultrasonically dispersed for 30 min, and then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 9.5:0.5.
[0041] Example 3
[0042] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0043] 0.002 mol of manganese chloride tetrahydrate, 0.005 mol of potassium fluoride dihydrate, 0.2 g of polyvinyl pyrrolidone, and 1.8 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30 min, then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 9:1.
[0044] Example 4
[0045] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0046] 0.002mol of manganese chloride tetrahydrate, 0.005mol of potassium fluoride dihydrate, 0.2g of polyvinyl pyrrolidone, and 0.466g of manganese dioxide nanoflowers were added to 36mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30min, then magnetically stirred for 1h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180°C for 12h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60°C for 12h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this example, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 7:3.
[0047] Example 5
[0048] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0049] 0.002 mol of tetrahydrated manganese chloride, 0.005 mol of dihydrated potassium fluoride, 0.2 g of polyvinyl pyrrolidone, and 0.3 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, and ultrasonically dispersed for 30 min, and then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 3:2.
[0050] Example 6
[0051] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0052] 0.002 mol of tetrahydrated manganese chloride, 0.005 mol of dihydrated potassium fluoride, 0.2 g of polyvinyl pyrrolidone, and 0.2 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, and ultrasonically dispersed for 30 min, and then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 1:1.
[0053] Example 7
[0054] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0055] 0.002 mol of manganese chloride tetrahydrate, 0.005 mol of potassium fluoride dihydrate, 0.2 g of polyvinyl pyrrolidone, and 0.133 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30 min, then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 2:3.
[0056] Example 8
[0057] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0058] 0.002 mol of tetrahydrated manganese chloride, 0.005 mol of dihydrated potassium fluoride, 0.2 g of polyvinyl pyrrolidone, and 0.085 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30 min, then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 3:7.
[0059] Example 9
[0060] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0061] 0.002 mol of manganese chloride tetrahydrate, 0.005 mol of potassium fluoride dihydrate, 0.2 g of polyvinyl pyrrolidone, and 0.05 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30 min, then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 1:4.
[0062] Example 10
[0063] The fluoride ion-induced manganese oxide composite material is prepared as follows:
[0064] 0.002 mol of manganese chloride tetrahydrate, 0.005 mol of potassium fluoride dihydrate, 0.2 g of polyvinyl pyrrolidone, and 0.022 g of manganese dioxide nanoflowers were added to 36 mL of polyethylene glycol in sequence, first ultrasonically dispersed for 30 min, then magnetically stirred for 1 h, and then the solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 12 h; after the reactor was naturally cooled to room temperature, it was centrifuged and washed, and dried in a vacuum oven at 60 ° C for 12 h to obtain a MnO2 / Mn2O3 / KMnF3 composite material. In this embodiment, in the composite material MnO2 / Mn2O3 / KMnF3, the mass ratio of MnO2:KMnF3 is 1:9.
[0065] Embodiment 11
[0066] (I) An aqueous magnesium ion capacitor with a fluoride ion induced manganese oxide composite material as a positive electrode material, the preparation method is as follows:
[0067] 1) Preparation of positive electrode: 40 mg of the MnO2 / Mn2O3 / KMnF3 composite material obtained in Example 1 was mixed evenly with 5 mg of polyvinylidene fluoride and 5 mg of Super P, and a small amount of NMP was added as a dispersion liquid to fully grind and mix the polyvinylidene fluoride and other substances. The slurry was then directly applied to the substrate carbon paper, dried in a vacuum drying oven at 60°C, and punched out using a punching machine to obtain a positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material;
[0068] 2) Preparation of negative electrode: 40 mg of activated carbon was mixed with 5 mg of polyvinylidene fluoride and 5 mg of Super P, and a small amount of NMP was added as a dispersion liquid. After mixing evenly, the slurry was directly applied on the substrate carbon paper, dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and punched using a punching machine to obtain a negative electrode sheet coated with activated carbon;
[0069] 3) Preparation of aqueous magnesium ion capacitors: The negative electrode sheet coated with activated carbon was placed in the center of the negative electrode shell, and then the diaphragm was placed in the negative electrode shell, and 200 μL of 0.5M MgSO4 electrolyte was dripped, and then one side of the positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material was contacted with the wetted diaphragm, and finally the gasket and shrapnel were placed, and a battery packaging machine was used to assemble it into a CR2032 button battery to obtain an asymmetric aqueous magnesium ion capacitor MnO2 / Mn2O3 / KMnF3 / / AC.
[0070] In addition, the comparative example uses manganese dioxide nanoflowers as the positive electrode material, and prepares an asymmetric aqueous magnesium ion capacitor MnO2 / / AC assembled with original MnO2 and activated carbon according to the above steps.
[0071] (II) Performance test
[0072] Figure 3 This is a time-voltage diagram of an asymmetric aqueous magnesium ion capacitor assembled from a fluoride ion-induced manganese oxide composite material and activated carbon prepared by the present invention. Figure 3 It can be seen that the discharge time of the fluorine ion-induced manganese oxide composite material obtained in Example 1 is significantly longer than that of the original single manganese-based material, and is increased by about 1300 seconds compared with the discharge time of the original manganese dioxide.
[0073] Figure 4: is a comparison chart of the specific capacitance of the asymmetric aqueous magnesium ion capacitor assembled with the fluoride ion induced manganese oxide composite material prepared by the present invention and activated carbon and the asymmetric aqueous magnesium ion capacitor assembled with the original manganese dioxide and activated carbon, Figure 4 It can be seen that the fluorine ion-induced manganese oxide composite material obtained in Example 1 has a specific capacitance of up to 209.56 F / g, compared with the original single manganese-based material, which is about 1.6 times greater than the original manganese dioxide.
Claims
1. A fluoride ion induced manganese oxide composite material, characterized in that: The preparation method comprises the following steps: 1) adding potassium permanganate and manganese sulfate into deionized water, dissolving them by magnetic stirring, performing hydrothermal reaction to obtain a precursor, and then calcining to obtain MnO2 nanoflowers; 2) The prepared MnO2 nanoflowers, manganese chloride, potassium fluoride and polyvinyl pyrrolidone are added to polyethylene glycol in sequence, and then ultrasonically dispersed and magnetically stirred to make them evenly dispersed. The solution is transferred to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction, centrifuged and washed, and dried to obtain a MnO2 / Mn2O3 / KMnF3 composite material.
2. The fluoride ion induced manganese oxide composite material according to claim 1, characterized in that: In the MnO2 / Mn2O3 / KMnF3 composite material, the mass ratio is MnO2:KMnF3=4:
1.
3. The fluorine ion induced manganese oxide composite material according to claim 1, characterized in that: In step 1), the hydrothermal reaction is carried out at 140° C. for 2 h; in step 2), the hydrothermal reaction is carried out at 180° C. for 12 h.
4. Use of the fluoride ion induced manganese oxide composite material according to claim 1, 2 or 3 as a positive electrode material in an aqueous magnesium ion capacitor.
5. The use according to claim 4, characterized in that: The method comprises the following steps: 1) Preparation of positive electrode: After the MnO2 / Mn2O3 / KMnF3 composite material is uniformly mixed with the binder and the conductive material, a small amount of NMP is added as a dispersion liquid. After uniform mixing, the slurry is directly applied on the substrate carbon paper, dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and punched using a punching machine to obtain a positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material; 2) Preparation of negative electrode: After the activated carbon is mixed with the binder and the conductive material, a small amount of NMP is added as a dispersion liquid. After mixing evenly, the slurry is directly applied on the substrate carbon paper, dried in a vacuum drying oven at 60°C for 12 hours, and then taken out and punched using a punching machine to obtain a negative electrode sheet coated with activated carbon; 3) Preparation of aqueous magnesium ion capacitors: Place the prepared negative electrode sheet coated with activated carbon into the center of the negative electrode shell, then place the diaphragm into the negative electrode shell, and drip the electrolyte to fully wet the diaphragm, then contact one side of the positive electrode sheet coated with the MnO2 / Mn2O3 / KMnF3 composite material with the wetted diaphragm, finally place the gasket and the shrapnel, and after packaging, obtain an aqueous magnesium ion capacitor.
6. The use according to claim 5, characterized in that: The binder is carboxymethyl cellulose or polyvinylidene fluoride.
7. The use according to claim 5, characterized in that: The conductive material is acetylene black or Super P.
8. The use according to claim 5, characterized in that: The electrolyte is any one of MgSO4 solution, MgCl2 solution and Mg(NO3)2 solution.
9. The use according to claim 8, characterized in that: The concentration of the electrolyte is 0.5 M, and the amount added is 200 μL.
10. The use according to claim 5, characterized in that: The diaphragm is any one of a glass fiber diaphragm, a polypropylene membrane, a filter paper diaphragm and a polymer semipermeable membrane.
Citation Information
Cited By
Method for preparing KMnF3 for capacitor based on manganese-potassium high-salinity wastewater
CN120829189A